THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN INSTILLING ISLAMIC CHARACTER VALUES IN SENIOR HIGH SCHOOLS 2 OKU REGENCY - Hariyanto, Joni; Marliat, Marliat; Ansori, Muhammad Rizal; Syahri, Syahri; Fahlepi, Reza (Jurnal Konseling Pendidikan Islam, 2025)
This research is motivated by the phenomenon of declining morality and Islamic character of the younger generation due to the rapid flow of globalization and the development of the times. The main purpose of this study is to find out how to instill character values based on Islamic Education at Senior High Schools 2 Oku Regency. This research uses a qualitative approach with data collection techniques through observation and documentation to obtain in-depth and valid information. The object of the research was carried out at Senior High Schools 2 Oku Regency, with the research subjects including grade XI students and Islamic Religious Education teachers who teach the subjects of Islamic Religious Education Lesson. The results of the study show that Islamic Religious Education teachers have a strategic role in instilling Islamic character values in students. These roles include roles as educators, supervisors, motivators, evaluators, and role models. Teachers actively foster positive habits of students, such as greetings, reciting prayers, and Asmaul Husna before and after learning, as well as carrying out religious activities such as congregational dzuhur prayers, muhadharah, and the reading of the Prophet’s prayers. However, there are several inhibiting factors in the value instilling process, including diverse student backgrounds, low student participation in religious activities, a less supportive school environment, and limited infrastructure. Nevertheless, PAI teachers are still committed to shaping students’ Islamic character consistently and sustainably.